OPTIMIZATION OF FINANCIAL PERSONNEL NUMBER IN ARMED FORCES OF THE REPUBLIC OF BELARUS - A. V. Bolshakova (Наука и техника)
The paper considers a problem pertaining to reduction of the Armed Forces of the Republic of Belarus and necessity to carry out economically reasonable reforms optimizing strength of financial personnel with the purpose to decrease its number but without undermining financial and operational activities of the Armed Forces as a whole. It has been proposed to optimize strength of financial personnel in the Armed Forces while executing organizational staff transformations such as introduction of a centralized accounting system for service personnel by an example of the Ministry of Defense of the Russian Federation.Normative for financial personnel strength of the supposed unified financial centre which is involved in accounting recordings on salary and other payments has been calculated on the basis of inter-branch standards. While taking as an example a conventional organization “B” with staff strength which is equal to the strength of the Armed Forces of the Republic of Belarus the possible efficiency in introduction of the centralized accounting system for service personnel has been determined in the paper. According to represented calculations reduction of financial personnel dealing with accounting recordings on salary and other payments in the whole organization “B” can constitute up to 60 persons with more than 200 branches which are carrying out independent payment accounting for personnel concerned.Dependence of strength normative on number of financial bodies, percentage of personnel receiving payments through a unified financial centre and concentration of financial and economic document circulation has been determined in the paper. It has been pointed out that it is not sufficient to determine quantitative indices in order to ensure an objective reflection of the efficiency of possible introduction of the centralized accounting system for service personnel in the Armed Forces. In order to obtain complete information it is necessary to consider qualitative changes paying a special attention to problems and possible ways of their solution. The paper describes problems pertaining to labour norming and it is of interest for financial-economic and organizational and mobilization bodies of the Armed Forces.